Road to ASEAN Political Security Community Vision 2025: Understanding Convergence and Divergence in ASEAN Voting Behaviors in the UNGA - Tangguh Chairil; Ratu Ayu Asih Kusuma Putri; Sukmawani Bela Pertiwi (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
While the ASEAN Political-Security Community (APSC) Blueprint 2025 envisages a centrality of regional architecture in responding to security challenges in the region, divided positions among the member states – mostly visible in the South China Sea dispute – have deepened the pessimism on the fate of APSC. Notwithstanding the persisting intra-ASEAN disunity, the organization has been projecting the goal of ASEAN centrality in the global political arena. The goal highlights ASEAN’s emerging role as the ‘hub’ of regional cooperation in Asia-Pacific hence cohesion is highly expected. This paper aims to examine ASEAN cohesion and how it aligns with the institution’s community-building project. To this aim, it primarily looks at the pattern of divergence and convergence in ASEAN voting behavior across security issues discussed in the UN General Assembly. It also underscores the underlying factors behind the emerging patterns. Using Agreement Index (AI), this paper found that ASEAN member states’ voting highly converges on colonialism, the law of the sea, the Mediterranean region, military expenditures, outer space, peace, and transnational crimes. Alternatively, voting diverges on resolutions related to arms transfer, counterterrorism, and armed conflict. Contributing factors to this pattern include member states' preferences, the identity, value, norms, and cognitive prior of the regional organization, as well as alliance and major powers’ preferences.